A Study of the Mental Wellbeing of Imprisoned Women in Iran - Khademi, Jalal; Kaj Björkqvist; Karin Österman (European Journal of Social Science Education and Research, 2019)
The study investigates the mental well-being of 35 women prisoners (mean age = 28.7, SD = 7.6) who all had received the capital punishment, in the Gorgan jail, northeastern Iran. Most of them had received their sentence for killing their husband. A control sample of 35 women of the same age from Gorgan was included. The respondents filled in a paper-and-pencil questionnaire. The imprisoned women scored higher than the controls on aggression, anxiety, and hostility; the controls scored higher than the imprisoned women on social support and emotional self-efficacy. The imprisoned women had, to a greater extent than the controls, a family history with addiction problems and suicidality.
Keywords: capital punishment, women, prison, mental wellbeing, Iran